Alzheimer’s disease pathogenetic progression is associated with changes in regulated retained introns and editing of circular RNAs - Arizaca Maquera, Karol Andrea; Welden, Justin Ralph; Margvelani, Giorgi; Miranda Sardón, Sandra C.; Hart, Samantha; Robil, Noémie; Hernandez, Alvaro Gonzalo; de la Grange, Pierre; Nelson, Peter T.; Stamm, Stefan (Frontiers in Molecular Neuroscience, 2023)
The genes contributing to Alzheimer’s disease (AD) progression are still not fully understood. We therefore determined mRNA and circular RNA (circRNA) expression in entorhinal and temporal cortex from seven subjects with Braak neurofibrillary tangle (NFT) stages I-VI. Across this pathogenetic progression represented by 3.2 billion reads, we detected 2,000 changes in mRNA transcripts and 3,000 changes in alternative exon usage. Using nanopore sequencing we identified 2,500 regulated retained introns that reside in polyadenylated RNA of which 131 correlated with Braak NFT stages. We detected 11,873 circRNAs of which 276 correlated with Braak NFT stages. Adenosine to inosine RNA editing increased about threefold in circRNAs during AD progression. Transfection experiments using circMAN2A1 that correlated with AD progression indicated that RNA editing promoted translation of circRNAs, activated translation of start codons out of frame with linear mRNAs and thus generated novel proteins. Our data identify regulated retained introns that correlate with Braak NFT stages and suggest a novel role for translated circRNAs in AD development.